Changing expression profiles of mRNA, lncRNA, circRNA, and miRNA in lung tissue reveal the pathophysiological of bronchopulmonary dysplasia (BPD) in mouse model. Issue 6 (25th February 2019) - Wang, Juan; Yin, Jing; Wang, Xingyun; Liu, Heng; Hu, Yin; Yan, Xiangyun; Zhuang, Bin; Yu, Zhangbin; Han, Shuping
Abstract: New perinatal care technologies have improved the survival rate of preterm neonates, but the prevalence of bronchopulmonary dysplasia (BPD), one of the most intractable problems in neonatal intensive care unit (NICU), remains unchanged. In present study, high‐throughput sequencing (HTS) was performed to detect the expression profiles of long noncoding RNAs (lncRNAs), messenger RNAs (mRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs) in hyperoxia‐induced BPD mouse model. Significant differentially expressed RNAs were selected and clustered between the BPD group and the control group. The results revealed that expressions of 1778 lncRNAs, 1240 mRNAs, 97 circRNAs, and 201 miRNAs were significantly altered in the BPD group. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed to predict the potential functions of differentially expressed RNAs. lncRNA‐mRNA and circRNA‐miRNA coexpression networks were constructed to detect their association with the pathogenesis of BPD. Our study provides a systematic perspective on the potential function of RNAs during BPD. Abstract : The sequence the expression profiles of long noncoding RNAs (lncRNA), messenger RNA (mRNA), circular RNA (circRNA), and microRNA (miRNA) in lung tissues of hyperoxia‐induced bronchopulmonary dysplasia (BPD) mice and air‐exposure mice; analyze the function of these RNAs with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG); construct lncRNA‐mRNA and circRNA‐miRNA coexpression network to find some genes that might be associated with the pathogenesis of BPD.